Effects of a ketogenic diet on body composition and strength in trained women. - Vargas-Molina, Salvador; Petro, Jorge Luis; Romance-García, Ángel Ramón; Kreider, Richard B.; Schienfeld, Brad J.; Bonilla, Diego A.; Benítez-Porres, Javier (BMC, 2020)
Background The effect of ketogenic diets (KD) on body composition in different populations has been investigated. More recently, some have recommended that athletes adhere to ketogenic diets in order to optimize changes in body composition during training. However, there is less evidence related to trained women. We aimed to evaluate the effect of a KD on body composition and strength in trained women following an eight-week resistance training (RT) program. Methods Twenty-one strength-trained women (27.6 ± 4.0 years; 162.1 ± 6.6 cm; 62.3 ± 7.8 kg; 23.7 ± 2.9 kg·m− 2) were randomly assigned to either a non-KD group (n = 11, NKD) or a KD group (n = 10, KD). Study outcomes included body composition as measured by dual-energy X-ray absorptiometry (DXA), strength levels measured using one maximum repetition (RM) in back squat and bench press (BP), and countermovement jump (CMJ) measured on a force plate. Results A significant reduction in fat mass was observed in KD (− 1.1 ± 1.5 kg; P = 0.042; d = − 0.2) but not in NDK (0.3 ± 0.8 kg; P = 0.225; d = 0.1). No significant changes in fat-free mass were observed in KD (− 0.7 ± 1.7 kg; P = 0.202; d = − 0.1) or NKD (0.7 ± 1.1 kg; P = 0.074; d = 0.2), but absolute changes favored NKD. No significant changes in BP were observed in KD (1.5 ± 4.6 kg; P = 0.329; d = 0.2), although significant changes were noted in the squat and CMJ (5.6 ± 7.6 kg; P = 0.045; d = 0.5 and 1.7 ± 1.9 cm; P = 0.022; d = 0.6, respectively). In contrast, NKD showed significant increases in BP (4.8 ± 1.8; P < 0.01; d = 0.7), squat (15.6 ± 5.4 kg; P = 0.005; d = 1.4) and CMJ (2.2 ± 1.7 cm; P = 0.001; d = 0.5). Conclusions Findings indicate that a KD may help to decrease fat mass and maintain fat-free mass after eight 8 weeks of RT in trained-women but is suboptimal for increasing fat-free mass.
Keywords: Dietas cetogénicas; Cuerpo humano - Composición; Acetonemia; Mujeres deportistas - Nutrición; Resistance training; Female; High-fat diet; Energy intake; Fat distribution